The Impact of Soft Skills Training and Managerial Support on Employee Career Development with Self-Confidence as a Mediator - Junaidi, Ahmad; Boyas, Jeziano Rizkita; Hamka, Rezky Amalia ? (Program Pascasarjana STIE Amkop Makassar, 2023)
This article investigates the multifaceted dynamics of employee career development within the Makassar office of PT. HM. Sampoerna, Tbk. The study focuses on the impact of soft skills training and managerial support, with self-confidence as a mediating variable. Through a comprehensive analysis, the research reveals that soft skills training significantly enhances employees' self-confidence, subsequently influencing their overall career development positively. Furthermore, self-confidence emerges as a significant mediator, amplifying the effects of both soft skills training and managerial support on career development. Notably, the direct influence of managerial support on career development is not statistically significant, prompting further exploration into leadership practices. These findings contribute valuable insights to the field of employee development, emphasizing the importance of holistic training programs and the pivotal role of self-confidence in shaping professional trajectories. The implications of this research provide organizations, including PT. HM. Sampoerna, Tbk, with actionable insights for refining talent development strategies and cultivating a workplace culture that empowers individuals toward sustained career success. Keywords: Employee Career Development, Soft Skills Training, Managerial Support, Self-Confidence